A New Civilization After Noah's Flood: An Exploration of the Development and Spread of Descendants to Three Continents in History and the Qur’an - Zulfikar, Zaky Zimmatillah; Fadhlurrahman, Zulfi; Bima Rahman Hakim (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2025)
Abstract The story of Noah's Ark is one of the most extensively studied historical narratives by researchers. Available literature remarkably envelops this tale, making it a phenomenal account. However, some texts conclude the narrative of Noah's Ark as soon as the great flood subsides. This has sparked significant curiosity among many. Therefore, this research aims to explore and analyze Noah's condition after the ark landed, what transpired after the great flood ended, who was on board the vessel, whether any humans survived outside Noah's Ark. These points form the core discussion and distinguish this study from previous research. The methodology employed in this study is a literature review, involving in-depth reading and analysis of the events surrounding Noah's Ark, Noah's descendants, and their subsequent dispersion. The findings of this research indicate that Noah's descendants spread across three major continents, becoming the pivotal transition point for civilization from the era of Adam. Keywords: Ark; Civilization; Noah; Transmission.   Abstrak Kisah Bahtera Nuh adalah salah satu cerita sejarah yang paling banyak dikaji oleh para peneliti. Literatur yang tersedia membungkus kisah ini dengan cara yang sangat menakjubkan, menjadikannya salah satu narasi fenomenal. Beberapa literatur hanya mengakhiri penceritaan Bahtera Nuh sampai air bah yang besar surut. Hal ini menimbulkan rasa ingin tahu yang besar bagi sebagian orang. Maka dari itu, penelitian ini bertujuan untuk mengeksplor dan menganalisis bagaimana keadaan Nuh setelah bahtera mendarat, apa yang terjadi setelah air bah besar berakhir, siapa saja yang berada di dalam kapal, dan apakah ada manusia yang selamat di luar Bahtera Nuh, menjadi pokok bahasan sekaligus menjadi pembeda dari penelitian sebelumnya. Metode yang digunakan dalam penelitian ini adalah kajian Pustaka, yaitu dengan membaca dan menganalisis peristiwa bahtera Nuh, keturunan Nuh dan penyebaran keturunan Nuh secara mendalam. Hasil penelitian ini menunjukkan bahwa penyebaran keturunan Nuh menyebar ke tiga benua besar dan menjadi kunci transisi peradaban dari peradaban Adam. Kata Kunci: Bahtera; Nuh; Peradaban; Penyebaran.